AUDIO QR FOR CLASS ATTENDANCE - Chin, Ching Voon (Universiti Malaysia Sarawak (UNIMAS), 2020)
Check-in attendance is common and important in every stage of our life. In our working life, we check-in and check-out when come on and off duties. This applies to student as well in taking class attendance. Being punctual is very important to improve efficiency and help people to build their personal image. With the rapid growth in technology, there are various existing ways to take attendance. This study investigates the most effective and suitable technology to be used on attendance taking system for the targeted UNIMAS students. During the study of this proposed system, a questionnaire regarding the current UNIMAS attendance system has been distributed to the students in UNIMAS. The results of the questionnaire are analyzed so that the attendance taking system can be improved to be more effective. The purpose of this project is to take class attendances by implementing the audio-based technology and record it to the system. By applying audio-based technology to the attendance system, lecturer can emit high-frequency sound. The high-frequency sound is to be received by the students to encode it and check-in their attendances. This project is proposed to solve the common problems faced by the students and lecturers in UNIMAS when using the current UNIMAS QR attendance system.